2001
DOI: 10.1590/s0104-11692001000400005
|View full text |Cite
|
Sign up to set email alerts
|

Retorno às atividades ocupacionais e sexuais após cirurgia de revascularização do miocárdio

Abstract: A prospective and longitudinal design was used to follow up the return to occupational and sexual activity among 17 males after coronary bypass surgery. The subjects' ages ranged from 35 to 73 years. Data collection was performed by using open interviews which were recorded in field notes during hospitalization after heart surgery and during 6 months following hospital discharge. Of the 14 patients who reported work and sexual activity before surgery, 8 were working again (p = 0.016), and 10 had returned to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
(19 reference statements)
0
8
1
9
Order By: Relevance
“…We found that, for the two support dimensions, the husbands/wives/partners were not the most mentioned sources, but relatives who did not live in the same house as the patients. In this respect, our study differs from other research that presents higher perceived availability and satisfaction with support, especially in the instrumental dimension, by people living with their husband/wife/partner (16)(17) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that, for the two support dimensions, the husbands/wives/partners were not the most mentioned sources, but relatives who did not live in the same house as the patients. In this respect, our study differs from other research that presents higher perceived availability and satisfaction with support, especially in the instrumental dimension, by people living with their husband/wife/partner (16)(17) .…”
Section: Discussioncontrasting
confidence: 99%
“…In the case of heart disease, the relatives' support in cardiac rehabilitation programs has been extremely important. After the cardiac event or therapeutic interventions, the support patients perceive, mainly when coming from their husband/ wife, has been related with favorable effects on their rehabilitation, making it possible for them to reassume their professional activities (3) and decreasing depression levels (1) . Individuals with greater social support have displayed better physical and mental performance after they were submitted to coronary artery bypass grafting (4) and heart transplantation (5) .…”
Section: Introductionmentioning
confidence: 99%
“…It is an important aspect to highlight, since the variable marital status could have been a confusing variable when analyzing social support according to gender. Some studies have suggested that there is a greater availability and satisfaction noticed for support, especially instrumental, by the people that have a companion (13)(14) . The authors mention that the subjects that are married or living with a significant other present higher support compared to those who are single, widowed or separated.…”
Section: Discussionmentioning
confidence: 99%
“…After the acute event or interventional procedure about 25% of patients resume their normal sex life with the same frequency and intensity, half of the patients resume their sex life at a reduced rate in terms of frequency and/or intensity and the remaining 25% never resume sexual activity [18]. There are number of well-established factors which can lead to the possibility of decreasing sexual activity after the cardiac events, including fear of coital death or reinfarction, dyspnea, angina, exhaustion, loss of libido, depression, impotence, anxiety, druginduced dysfunction and risk factors such as diabetes, hypertension, dyslipidemia, smoking and sedentary life style [19]. The aim of the present study was to evaluate the HRQoL in overall of 719 consecutive CAD patients, admitted for specialized cardiovascular rehabilitation at the Institute for Treatment and Rehabilitation "Niška Banja", Niš, Serbia, within 3 months post CAD and to assess their general condition with regards to treatment strategy, sex, age and self-reported exposure to stress.…”
Section: Introductionmentioning
confidence: 99%